Therapeutic efficacy of Centratherum anthelminticum in subclinical mastitis: A biochemical and hematological assessment in lactating cattle - Muhammad Adil; Farrah Deeba; Muhammad Tariq; Muhammad Usman; Saba Saeed; Eliana Ibáñez-Arancibia; Patricio De los Ríos-Escalante; Muhammad Safdar (Veterinary World, 2025)
Background and Aim: Subclinical mastitis (SCM) in dairy cattle significantly compromises milk quality, animal health, and farm profitability, often remaining undetected due to the absence of clinical signs. The increasing antimicrobial resistance associated with conventional treatments highlights the need for effective alternatives. This study aimed to evaluate the therapeutic potential of Centratherum anthelminticum (CA), alone and in combination with tylosin, in managing SCM in lactating cows.